Psychoeducation for adult ADHD: a scoping review about characteristics, patient involvement, and content - Pedersen, Henrik; Skliarova, Tatiana; Pedersen, Sindre Andre; Gråwe, Rolf W.; Havnen, Audun; Lara-Cabrera, Mariela L. (BMC Psychiatry, 2024)
Abstract Background Psychosocial interventions such as psychoeducation are increasingly being used to treat adult ADHD, both as an alternative and as a supplement to pharmacotherapy. A thorough overview of the literature on psychoeducation for adult ADHD is lacking. The objectives of this scoping review were therefore to identify the characteristics of psychoeducation interventions designed for adults with ADHD, examine how the patient experience or perspective is considered during the intervention’s development and implementation, determine the typical themes covered, and explore how ‘psychoeducation’ is defined in these interventions. Methods A comprehensive search was performed to identify records in MEDLINE, Embase, PsycINFO, Web of Science, Cochrane CENTRAL, AMED, and ClinicalTrials.gov. Two or more reviewers were included in every step of the screening process and the final selection of included studies. The Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist (Supplementary Material 1) was used to report the results, and the framework developed by Arksey and O’Malley was used as a guide throughout the scoping process. Results A total of 2121 records were identified through the literature search. After screening and full-text analysis, ten studies were included for final analysis. Most studies were conducted in Europe and followed a group format. Seven main themes were identified: Information about the diagnosis, treatment options, somatic health and ADHD, the insider perspective, ADHD and social life, coping and psychological skills, and ADHD and work. There was significant overlap in themes covered, but coverage of each theme varied. Themes deemed important by newer research, such as sexuality and gender-specific issues, were missing. Only one intervention involved patients in its development and implementation, and two interventions involved family members. There was variation in how psychoeducation was defined in the included studies, and the implications of this are discussed. Conclusion The literature on psychoeducation for adult ADHD is not ready for any systematic effect estimation. Before such estimations are conducted, a shared understanding and definition of psychoeducation are needed. The involvement of end users in the development and delivery of interventions may aid reach this goal but results from this review indicate that such practices are rare.